2023
DOI: 10.1108/jcp-04-2022-0012
|View full text |Cite
|
Sign up to set email alerts
|

Professional boundary violations in prisons: a scoping review of the literature

Abstract: Purpose Professional boundary violations – intentional blurring, minimising or exploiting of institutions’ ethical and legal frameworks – have the potential to cause significant harm to prisoners, staff, prison systems and the public. There has been little empirical research on the nature, extent and impact of boundary violations in UK prisons. The purpose of this paper is to synthesise and critically review studies which have sought to explore, measure and predict boundary violative behaviour, with a view to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(163 reference statements)
0
3
0
Order By: Relevance
“…Regarding boundary violations, and its connection with stress and burnout, as explored in the current study, literature is scarce. This is expected considering that boundary violations are an emerging research topic with little published research and stress and burnout are among several factors that can potentially contribute to this behaviours (Kelly and Potter, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding boundary violations, and its connection with stress and burnout, as explored in the current study, literature is scarce. This is expected considering that boundary violations are an emerging research topic with little published research and stress and burnout are among several factors that can potentially contribute to this behaviours (Kelly and Potter, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This has been noted as a particular concern when it comes to the relationships between incarcerated men and female prison staff. In fact, a recent review of the staff boundary violation literature found that a common policy recommendation is to restrict cross-sex staff employment in carceral facilities (Kelly & Potter, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This measure was included because of its implications for the management perspective. That is, some literature suggests that incarcerated people, particularly men, may attempt to establish inappropriate relationships with female employees to facilitate the introduction of contraband (Kelly & Potter, 2023; Worley & Worley, 2011). To the extent this occurs, it clearly undermines the efficacy of a prison's management structure.…”
Section: Current Studymentioning
confidence: 99%